Fonotaktik dan Pembentukan Suku Kata Bahasa Sangir - Kasiahe, Evi Martika D. (Universitas Sam Ratulangi, 2019)
Sangihe ethnic surnames have numerous morphological processes, but have not been a major concern for linguists. Previous research from Bawole (1981) regarding the morphology of Sangihe language also had not analyzed this issue. In this research, researchers analyzed names morphologically in particular affixation and reduplication. The data in this research were collected through two methods, namely observation method with the technique of observing by visiting village’s office and collecting data regarding surnames. Secondly, interview with elicitation technique are employed to four informants to comprehend the meaning of the collected data of surnames. Data analysis was done through distributional method and was based on the morphological theory of Aronoff and Fudeman (2011). This research aims to explain three things, namely the affixation process and reduplication process of Sangihe ethnic surnames. In affixation it is found that a similar affix can produce different grammatical meanings depending on the class of words it adheres to and that Sangihe ethnic surnames found that a form of partial reduplication, namely repetition of the first phoneme of the basic form.Keywords: morphology, surname, ethnic, sangihe